Technological power, complex systems, and boundary objects in global energy transitions - Ahlborg, Helene (Frontiers in Human Dynamics, 2024)
This research topic makes a case for why the field of political ecology (PE) would benefit from deep engagement with technological power and exemplifies this within the domain of energy studies and ongoing energy sector transformation. Technology is not among the core interests and traditional PE topics – and is thus typically left aside or treated as a black box. The argument here is that this omission undermines the analytical power and relevance of the field. Technology is the central mechanism whereby socionatures evolve and how relationships are negotiated and enacted. The attitude towards things technical is partly based on the idea that technologies are just artefacts of little interest. Cross-field dialogue is also hindered by perceived ontological conflicts. This topic draws on work from philosophy of technology and sociotechnical systems theory to introduce a dynamic understanding of technological power. Seeing what technology does and has the potential to do requires looking beyond the common emphasis on dominance and control, to the myriad ways in which technologies shape our everyday lives, ontologies and imagining of the future. Taking on a contentious concept, I advocate for the use of “systems” as a boundary object suitable for cross-field dialogue. As an analytical construct without inherent scale, it works as a framing device for moving power and knowledge claims to the forefront, while also allowing dialogue outside academia.